Buddhism the middle way of compassion - Henry, Oliver (Colorado : Delphi Production [production company] ; Illinois : United Learning [distributor], 1993)
This program shot on location in India, Nepal, Thailand, and Japan explores the history, the development, the art, and the influence of Buddhism in the world
Video is accompanied by a teacher's guide and 7 pages of blackline masters
Editor, Paul Christman
Narrator, Keith Jackson
Keywords: Buddhism; Buddhism -- History